Cultivating Environmental Care Character through Sekolah Alam Indonesia: A Literature Review - Feri Dwi Jayanti; Rizki Achmad Husaeni; Prince Clinton Immanuel Christian Damanik; Anastasia Arta Uli; Mohammad Idham Chaled (Universitas Muhammadiyah Mataram, 2026)
Abstract: Environmental awareness among students is still relatively low, necessitating an educational model capable of fostering a sustainable ecological character. Sekolah Alam offer an alternative education that integrates the learning process with nature through a contextual approach and direct experience. This study seeks to review and analyses the results of previous research on the role of Sekolah Alam in shaping students' environmental character. This study used a systematic literature review method on scientific articles published between 2024-2025 that discussed contextual learning, the integration of religious values, and the application of experiential learning in Indonesian Sekolah Alam. The process of searching, selecting, and analyzing articles follows the PRISMA procedure with measurable criteria, analyzed using a thematic analysis approach and concept-centric review to ensure comprehensive and transparent findings. The results of the study indicate that the integration of environmental values into the curriculum, the role of teachers as facilitators, and learning activities based on real experiences contribute significantly to the formation of students' ecological awareness and behaviour. Thus, Sekolah Alam can be seen as an effective sustainable education model in fostering environmental character from an early age. Sekolah Alam’s curriculum, supported by the maximum role of teachers, can be an alternative for other schools to foster environmental character.Abstrak: Kesadaran peduli lingkungan di kalangan pelajar masih tergolong rendah, sehingga diperlukan model pendidikan yang mampu menumbuhkan karakter ekologis secara berkelanjutan. Sekolah Alam hadir sebagai alternatif pendidikan yang mengintegrasikan proses belajar dengan alam melalui pendekatan kontekstual dan pengalaman langsung. penelitian ini berupaya meninjau dan menganalisis hasil-hasil penelitian terdahulu tentang peran Sekolah Alam dalam membentuk karakter peduli lingkungan peserta didik. Penelitian ini menggunakan metode studi literatur sistematis (systematic literature review) terhadap artikel ilmiah terbit pada tahun 2024-2025 yang membahas pembelajaran kontekstual, integrasi nilai keagamaan, dan penerapan experiential learning di Sekolah Alam Indonesia. Proses penelusuran, seleksi, dan analisis artikel mengikuti prosedur PRISMA dengan kriteria terukur, dianalisis menggunakan pendekatan analisis tematik serta concept centric review agar temuan komprehensif dan transparan. Hasil kajian menunjukkan bahwa integrasi nilai peduli lingkungan dalam kurikulum, peran guru sebagai fasilitator, serta kegiatan belajar berbasis pengalaman nyata berkontribusi signifikan terhadap pembentukan kesadaran dan perilaku ekologis peserta didik. Dengan demikian, Sekolah Alam dapat dipandang sebagai model pendidikan berkelanjutan yang efektif dalam menumbuhkan karakter peduli lingkungan sejak usia dini. Kurikulum Sekolah Alam didukung dengan peran guru yang maksimal dapat menjadi alternatif bagi sekolah-sekolah lain untuk menumbuhkan karakter peduli lingkungan.